2015
DOI: 10.1177/0886260515596333
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Parental Conflict Resolution Strategies on Hispanic College Women’s Experiences With Verbal Aggression

Abstract: The study investigates the relation between interparental verbal aggression, parent-daughter verbal aggression, and verbal aggression in female Hispanic college student's dating relationships ( N = 599). Results showed that mothers' high levels of verbal conflict with fathers were predictive of having high levels of verbal conflicts with their daughters. This in turn, predicted daughters' use of verbal conflict with their intimate partner. Similarly, fathers' high levels of verbal conflict with mothers were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
3
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(84 reference statements)
4
3
0
3
Order By: Relevance
“…The study also found that fathers’ use of VA toward the daughter influences mothers’ use toward the daughter but not vice versa. The finding supports prior research findings about the influence of paternal machismo behaviors on familial conflict (Dietrich & Schuett, 2013; Oramas et al, 2015). Prior research findings would suggest, more specifically, the ways in which a father, that is, the dominant force in the family, can subordinate all other members, including the wife (Skuja & Halford, 2004; Snethen & Van Puymbroeck, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The study also found that fathers’ use of VA toward the daughter influences mothers’ use toward the daughter but not vice versa. The finding supports prior research findings about the influence of paternal machismo behaviors on familial conflict (Dietrich & Schuett, 2013; Oramas et al, 2015). Prior research findings would suggest, more specifically, the ways in which a father, that is, the dominant force in the family, can subordinate all other members, including the wife (Skuja & Halford, 2004; Snethen & Van Puymbroeck, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Studies show that spouses often equally engage in IPV toward their partner and for similar reasons, where one partners' aggression is responded to with aggression (Atkin et al, 2002;Infante et al, 1990;Medeiros & Straus, 2006). In accordance with the current research, a study with a sample of Hispanic college women found that parental use of VA toward one another is correlated and also influences their use of VA toward their daughters (Oramas et al, 2015). The current study, therefore, also demonstrates reciprocity of verbal violence.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations